Framework analysis for Vision Scientists: a clear step-by-step guide - Somerville, Joel; Jonuscheit, Sven; Strang, Niall (Scandinavian Journal of Optometry and Visual Science, 2023)
Vision sciences has traditionally been a quantitative discipline. However, to fully capture all aspects of clinical vision care, researchers increasingly need to be conversant in both quantitative and qualitative methodologies. This has resulted in qualitative methodologies becoming more common in vision sciences research literature. From the authors’ perspective, vision researchers often struggle to identify suitable qualitative methodologies when coming from a tradition of a realist ontology, or the view that independent truth exists. This study explores the ontological and epistemological considerations when approaching qualitative research in vision sciences and proposes framework analysis as a qualitative methodology that is accessible for vision scientists. Framework analysis is a flexible and highly utilitarian qualitative analysis method which complements quantitative methodologies. This paper also presents a step-by-step guide for conducting framework analysis in a logical, transparent, and repeatable way that will provide a clear audit trail of how results are obtained from subjective data. This is done using a worked example from a recent eye care study.